Optimization studies on foaming characteristics of industrial solvent - Degarajan, Ravishanker (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
In a Natural Gas Liquefaction, there are many steps that the gas has to pass before being liquefied and stored. One of this is the Gas Treating Unit, where an acid gas is removed from the flowing gas. The main reason for gas removal is to avoid blockage in the Liquefaction Unit. In the Gas Treating Unit, amine solution is used as solvent to remove these gases. The main concern here is that the amine solution, when mixed with entrained heavy/liquid hydrocarbon from the gas stream, form foams. The probable reasons that cause foaming are presence of hydrocarbon liquid, iron sulfide (FeS), oil and grease or dust in the solution (observed by fluctuating pressure drop across the trays), high carbon dioxide loading, improper regeneration of amine solution, and decomposition of antifoam agents that has been added. Foaming leads inefficiency in sulphur absorption and tendency of amine carryovers increases. The main objective of this project is to determine ways of minimizing the foam formation by varying the operation conditions such as gas flow rate, presence of impurities and usage of antifoam agent with the aid of Design Expert software. This can be done by determining the height of foam developed by each solution tested. Based on the optimum condition for the production a mixture solution that has the lowest foaming tendency is at a volume of 106.17 mL, with an air flow rate of 0.54 L/min and lastly with 1.38 % as the dosage of anti foaming agent in the mixture solvent, a 0 cm of foam height is obtained